Speech Discrimination Tasks: A Sensitive Sensory and Cognitive Measure in Early and Mild Multiple Sclerosis - Iva, Pippa; Fielding, Joanne; Clough, Meaghan; White, Owen; Godic, Branislava; Martin, Russell; Rajan, Ramesh (Frontiers in Neuroscience, 2020)
There is a need for reliable and objective measures of early and mild symptomology in Multiple Sclerosis (MS), as deficits can be subtle and difficult to quantify objectively in patients without overt physical deficits. We hypothesised that a speech-in-noise (SiN) task, which is sensitive to demyelinating effects on precise neural timing and diffuse higher-level networks required for speech intelligibility, would be a useful tool for monitoring sensory and cognitive changes in early MS. The objective of this study was to develop a SiN task for clinical use that sensitively monitors disease activity in early (< 5 years) and late (> 10 years) stages of MS subjects with mild severity (Expanded Disability Status Scale (EDSS) score < 3). Pre-recorded Bamford-Kowal-Bench sentences and isolated keywords were presented at five signal-to-noise ratios (SNR) in one of two background noises: speech-weighted noise and eight-talker babble. All speech and noise were presented via headphones to controls (n = 38), early MS (n = 23) and late MS (n =12) who were required to verbally repeat the target speech. MS subjects also completed extensive neuropsychological testing which included: Paced Auditory Serial Addition Test, Digit Span Test and California Verbal Learning Test. Despite normal hearing thresholds, subjects with early and late mild MS displayed speech discrimination deficits when sentences and words were presented in babble – but not speech-weighted noise. Significant correlations between SiN performance and standardised neuropsychological assessments indicated that MS subjects with lower functional scores also had poorer speech discrimination. Furthermore, a quick five-minute task with words and keywords presented in multi-talker babble at an SNR of -1dB was 82% accurate in discriminating mildly impaired MS individuals (median EDSS=0) from healthy controls. Quantifying functional deficits in mild MS will help clinicians to maximise the opportunities to preserve neurological reserve in patients with appropriate therapeutic management, particularly in the earliest stages. Given that physical assessments are not informative in this fully ambulatory cohort, a quick five-minute task with words and keywords presented in multi-talker babble at a single SNR could serve as a complementary test for clinical use due to its ease of use and speed.